Equivalent inpatient mortality among direct-acting oral anticoagulant and warfarin users presenting with major hemorrhage. Issue 185 (January 2020) - Bialkowski, Walter; Tan, Sylvia; Mast, Alan E.; Kiss, Joseph E.; Kor, Daryl; Gottschall, Jerome; Wu, Yanyun; Roubinian, Nareg; Triulzi, Darrell; Kleinman, Steve; Choi, Young; Brambilla, Donald; et al.
Abstract: Background: Extrapolation of clinical trial results comparing warfarin and direct-acting oral anticoagulant (DOAC) users experiencing major hemorrhage to clinical care is challenging due to differences seen among non-randomized oral anticoagulant users, bleed location, and etiology. We hypothesized that inpatient all-cause-mortality among patients presenting with major hemorrhage differed based on the home-administered anticoagulant medication class, DOAC versus warfarin. Methods: More than 1.5 million hospitalizations were screened and 3731 patients with major hemorrhage were identified in the REDS-III Recipient Database. Propensity score matching and stratification were used to account for potentially confounding factors. Results: Inpatient all-cause-mortality was lower for DOAC (HR = 0.60, 95%CI 0.45–0.80, p = 0.0005) before accounting for confounding and competing events. Inpatient all-cause-mortality for 1266 propensity-score-matched patients compared using proportional hazards regression did not differ (HR = 0.84, 95%CI 0.58–1.22, p = 0.36). Inpatient all-cause-mortality in stratified analyses (warfarin as reference) produced: HR = 0.69 (95%CI 0.31–1.55) for traumatic head injuries; HR = 1.10 (95%CI 0.62–1.95) for non-traumatic head injuries; HR = 0.62 (95%CI 0.20–1.94) for traumatic, non-head injuries; and HR = 0.69 (95%CI 0.29–1.63) for non-traumatic, non-head injuries. Mean time to discharge was shorter for DOAC (HR = 1.17, 95%CI 1.05–1.30, p = 0.0034) in the propensity score matched analysis. Plasma transfusion occurred in 42% of warfarin hospitalizations and 11% of DOAC hospitalizations. Vitamin K was administered in 63% of warfarin hospitalizations. Conclusions: After accounting for differences in patient characteristics, location of bleed, and traumatic injury, inpatient survival was no different in patients presenting with major hemorrhage while on DOAC or warfarin. Highlights: Studies of DOAC outcomes following major hemorrhage have bias, confounding, and competing events. We compared DOAC and warfarin users with major hemorrhage accounting for these factors. All-cause inpatient mortality was no different; hospital length of stay was shorter for DOAC. Use of plasma and vitamin K was greater among warfarin users.